Principal’s Leadership in Developing Teacher’s Professionalism - Pratiwi, Tri Wahyuni; Kristiawan, Muhammad; Wardiah, Dessy (Yayasan Sembilan Pemuda Indonesia, 2023)
The role of the school as a place to educate and develop students’ potential must have leaders who can analyze school needs and solve problems that arise. The poor quality of teachers is a problem that cannot be separated from the role of the principal in the world of education. The writer finds that many educators are not professional in learning mastery. The purpose of this study was to determine the principal’s leadership in fostering teacher professionalism at SD Negeri 17 Banyuasin 1 and its supporting and inhibiting factors. This study uses a qualitative method, namely descriptive analysis. Data collection techniques used are interviews and observation. The results show the principal’s ability to lead, inspire, motivate, supervise, guide, find, and give orders to his staff members. The obstacles can be in the form of facilities and infrastructure in supporting learning, as well as the lack of attention from parents.